Industrially viable technique for the preparation of HDPE/fly ash composites at high loading: Thermal, mechanical, and rheological interpretations. Issue 11 (16th November 2017) - Verma, Pawan; Kumar, Anuj; Chauhan, Sampat Singh; Verma, Meenakshi; Malik, Rajender Singh; Choudhary, Veena
ABSTRACT: This article describes an industrially viable melt blending approach for the preparation of high‐density polyethylene (HDPE)/fly ash composites having high loading of fly ash (FA) (up to 25 wt %). In this approach, solvent was used to enhance the mixing of FA in HDPE matrix. FA coated on the outer surface of HDPE granules using solvent is an economical technique for the incorporation of high loading of FA using conventional twin screw extruder. Herein, the effect of HDPE reinforced with FA on thermal, rheological, and mechanical properties has been investigated. Incorporation of FA in HDPE matrix resulted in higher storage modulus ( E ′), loss modulus ( E ″), and complex viscosity (η*) as compared to neat polymer. Tensile and flexural moduli were also found to increase (∼47% and ∼66%, respectively) with the addition of FA (25 wt %). However, the elongation at break of HDPE reduced as the rigid spherical FA particles do not undergo elongation. The dispersion of FA within the polymer matrix and interaction of FA with HDPE were investigated using scanning electron microscopy. Rheological and mechanical properties of the composites were also correlated with the morphology. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 45995. Abstract :